THE USE OF ZOONYMS IN THE NAMES OF SPORTS TEAMS - Buriev Dilmurod Arzimurodovich (International Scientific and Current Research Conferences, 2025)
This article studies the phenomenon of using zoonyms (animal names) in the names of sports teams. Animal words are often found in team names, reflecting the strength, agility or other positive qualities of the team. The article presents the reasons for this trend, linguistic and psychological aspects, as well as an analysis of zoonyms found in the names of sports clubs in different countries. It also discusses the impact of zoonyms on brand creation, attracting fans and the image of the team.